6G and Internet of Things: a survey. Issue 2 (3rd April 2021) - Kim, Jin Ho
Abstract : The 5G networks which have begun to spread worldwide are expected to contribute to an increase in the use of Internet of Things (IoT) technologies and applications, which require massive connectivity, security, and ultra-low latency. However, it is known that 5G alone is not sufficient for many IoT devices to exchange various types of data in real time. These constraints promote the emergence of 6G technologies which can support higher network capacity, lower latency, and faster data transmission than 5G networks. To understand the current trends in 6G research and their relation to IoT, this paper introduces the main drivers of 6G technology, describes 6G's enabling technologies, summarizes current 6G research, and introduces the possible applications of 6G to IoT technologies and service areas.